A firm-industry analysis of services versus manufacturing - Esteban Fernández Vázquez; Vicente López-López; Carlos M. Jardón; Susana Iglesias-Antelo (European Research on Management and Business Economics (ERMBE), 2022)
In the literature on the firm-industry debate to explain organizational performance the firm effect has been more supported than the industry effect by empirical studies, mainly focused on manufacturing firms and long time periods. Unfortunately, little attention has been paid to the service sector. In this paper we study separately manufacturing and services in a broad sample of Spanish companies. We observe that in manufacturing the firm effect outweighs the industry effect while in services the opposite is the case in a ten-year period. However, when we split the time horizon into two five-year sub-periods, this behavior only remains in the second one, of moderate economic growth. In the first one, of strong economic growth, the firm effect prevails for both manufacturing and services. These findings underline the importance of the industry effect for services, suggesting that such effect may have been underestimated in the literature, as well as that of the level of economic growth specially for the decision-making of practitioners.
Keywords: G30; M21; L16; L25; 650; Firm effect; Industry effect; Manufacturing; Performance; Services